2023
DOI: 10.3390/molecules28030949
|View full text |Cite
|
Sign up to set email alerts
|

Modified Technogenic Asphaltenes as Enhancers of the Thermal Conductivity of Paraffin

Abstract: The low thermal conductivity of paraffin and other organic phase change materials limits their use in thermal energy storage devices. The introduction of components with a high thermal conductivity such as graphene into these materials leads to an increase in their thermal conductivity. In this work, we studied the use of inexpensive carbon fillers containing a polycyclic aromatic core, due to them having a structural similarity with graphene, to increase the thermal conductivity of paraffin. As such fillers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…It is noteworthy that the ASP2 molecule resembles the structure of so-called “technogenic” asphaltenes isolated from ethylene tar samples in ref. 16 and 28. The aliphatic periphery of this molecule consists of several methyl and ethyl groups, so that the ASP2 molecular weight amounts to about 500 g mol −1 in accordance with a peak molecular weight value observed through the matrix assisted laser desorption/ionization (MALDI) spectroscopy for the most probable “technogenic” asphaltene molecules considered in ref.…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…It is noteworthy that the ASP2 molecule resembles the structure of so-called “technogenic” asphaltenes isolated from ethylene tar samples in ref. 16 and 28. The aliphatic periphery of this molecule consists of several methyl and ethyl groups, so that the ASP2 molecular weight amounts to about 500 g mol −1 in accordance with a peak molecular weight value observed through the matrix assisted laser desorption/ionization (MALDI) spectroscopy for the most probable “technogenic” asphaltene molecules considered in ref.…”
Section: Methodssupporting
confidence: 84%
“…Recent experiments and computer simulations have suggested that asphaltenes can be used as fillers for paraffin-based phase-change materials. [14][15][16] These materials are promising for developing domestic thermal energy storage systems, but their low thermal conductivity limits their performance by reducing charging and discharging rates. Adding asphaltenes to paraffin has been found to increase its thermal conductivity, thus enhancing the practical prospects of these materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations